Involvement of vestibular organs in idiopathic sudden hearing loss with vertigo: An analysis using oVEMP and cVEMP testing. Issue 5 (May 2015) - Fujimoto, Chisato; Egami, Naoya; Kinoshita, Makoto; Sugasawa, Keiko; Yamasoba, Tatsuya; Iwasaki, Shinichi
Highlights We investigated the extent of vestibular lesions in idiopathic sudden hearing loss (ISHL) with vertigo using cervical and ocular vestibular evoked myogenic potential (cVEMP, oVEMP) testing and caloric testing. The percentage of abnormal responses in patients with ISHL with vertigo was highest in the cVEMP test, followed by the oVEMP and caloric tests. The vestibular end organs closest to the cochlea tended to be preferentially affected in ISHL with vertigo.